2017
DOI: 10.3892/or.2017.5393
|View full text |Cite
|
Sign up to set email alerts
|

miR520c blocks EMT progression of human breast cancer cells by repressing STAT3

Abstract: Breast cancer is one of the most malignant diseases world-wide and it ranks the first among female cancers. Masses of intrinsic and extrinsic factors, especially the inflammatory factors can lead to breast cancer. Aberrant activation and accumulation of key molecules can lead to inflammation associated carcinogenesis. The signal transducers and activators of transcription 3 (STAT3) is one of them. Therefore, to evaluate the novel molecular mechanisms, STAT3 has become our focus for breast cancer targeted thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…As illustrated in Table II, the miR-520 family (miR-520a, b, c, d and e) was commonly identified in the three databases, and miR-520c-3p was predicted by all three databases to regulate the 3'-UTR of IL-8. (22,23). As shown in Fig.…”
Section: Bioinformatic Analysis Of Il-8 3'-utrmentioning
confidence: 84%
“…As illustrated in Table II, the miR-520 family (miR-520a, b, c, d and e) was commonly identified in the three databases, and miR-520c-3p was predicted by all three databases to regulate the 3'-UTR of IL-8. (22,23). As shown in Fig.…”
Section: Bioinformatic Analysis Of Il-8 3'-utrmentioning
confidence: 84%
“…STAT family has a variety of transcription factors and they can play significant roles in regulating cell proliferation, differentiation, apoptosis, and inflammatory responses (Wang, Wei et al, ). STAT3 is a transcription factor member belonging to STATs.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines can activate a series of EMT‐inducing transcription factors and thus act pleiotropically to choreograph the complex EMT program which eventually leads to the disruption of cell‐cell adherent junctions and the cell‐ECM adhesions . It has been demonstrated that the EMT can endow cancer cells with the migratory and invasive capabilities associated with metastatic competence …”
Section: Introductionmentioning
confidence: 99%
“…4 It has been demonstrated that the EMT can endow cancer cells with the migratory and invasive capabilities associated with metastatic competence. [5][6][7][8] Chemokines are a superfamily of secreted proteins involved in inflammatory and immunoregulatory processes. Monocyte chemoattractant protein-1/CCL2 is one of the key chemokines that displays chemotactic activity for monocytes and basophils but not for neutrophils or eosinophils.…”
mentioning
confidence: 99%